Pathogenic aberrations revealed exclusively by single nucleotide polymorphism (SNP) genotyping data in 5000 samples tested by molecular karyotyping. Issue 12 (29th October 2011) - Bruno, D L; White, S M; Ganesamoorthy, D; Burgess, T; Butler, K; Corrie, S; Francis, D; Hills, L; Prabhakara, K; Ngo, C; Norris, F; Oertel, R; et al.
Abstract : Background: Several recent studies have demonstrated the use of single nucleotide polymorphism (SNP) arrays for the investigation of intellectual disability, developmental delay, autism or congenital abnormalities. In addition to LogR 'copy number' data, these arrays provide SNP genotyping data for gene level autozygosity mapping, estimating low levels of mosaicism, assessing long continuous stretches of homozygosity (LCSH), detection of uniparental disomy, and 'autozygous' regions. However, there remains little specific information on the clinical utility of this genotyping data. Methods: Molecular karyotyping, using SNP array, was performed on 5000 clinical samples. Results: Clinically significant 'LogR neutral' genotyping abnormalities were detected in 0.5% of cases. Among these were a single case of chimerism, 12 cases with low level chromosome mosaicism, and 11 cases with an LCSH associated with uniparental disomy. In addition, the genotyping data revealed several LCSH associated with clinically relevant 'recessive type' genetic defects. Conclusions: These results demonstrate the utility of SNP genotyping data for detection of clinically significant abnormalities, including chimerism/mosaicism and recessive Mendelian disorders associated with autozygosity. The incidence of clinically significant low level mosaicism inferred from these cases suggests that this has hitherto been underestimated and chromosome mosaicism frequently occurs in the absence of indicative clinical features. The growing appreciation among clinicians and demand for SNP genotyping data poses significant challenges for the interpretation of LCSH, especially where there is no detailed phenotypic description to direct laboratory analysis. Finally, reporting of unexpected or hidden consanguinity revealed by SNP array analysis raises potential ethical and legal issues.